PROFIL PEMULUNG DI KELURAHAN PARUPUK TABING KECAMATAN KOTO TANGAH KOTA PADANG - Crisyah Simanulang; surtani surtani (JURUSAN GEOGRAFI FIS UNP, 2020)
This study aims to determine the age, education, income, health conditions, number of children and education of scavengers and the reasons for being scavengers. This type of research is descriptive quantitative. The study population was scavengers in the Village of Parupuk Tabing. The research sample uses the Snowball Sampling technique, by determining key informants and showing research subjects. 26 scavengers sample. Data collection using observation and questionnaire distribution techniques. Data analysis technique with a percentage. Results: average age of productive waste pickers is 51 years old (34.62%), scavenger education is low because graduating and not graduating from junior high is (38.46%). scavenger income is low because it is below Rp 1,500,000 per month (61.53%). If a person suffering from a mild disease scavengers go to a health center using BPJS (76.93%), the number of scavengers is an average of 4 people (57.69%) children's education is quite good because there are many in the condition of schooling (72.85%) and the reasons become a scavenger because of limited capital to open another business (62.24%).